Coblation vs. dissection tonsillectomy: a prospective randomized study comparing surgical and clinical outcomes - Vyas, Shifa; Sharma, Pritosh; Sharma, Nitin; Makwana, Abhijit; Goyal, V. P. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: The objective of this study is to compare operative time, intraoperative bleeding, postoperative pain between coblation and dissection tonsillectomy. Methods: A total of 62 patients who met the inclusion criteria were divided into two groups according to the surgical procedure they went through. Surgical time intraoperative blood loss, postoperative pain, postoperative regaining of activity and any episode of postoperative bleeding were noted in both the groups and compared. Results: Coblation tonsillectomy fared better than dissection tonsillectomy in terms of having less intraoperative blood loss, less postoperative pain. Patients who underwent coblation assisted tonsillectomy also had earlier return to normal activities. Though the time required for coblation tonsillectomy was more than dissection tonsillectomy there were no episodes of postoperative bleeding in subjects who underwent coblation tonsillectomy. Conclusions: Coblation assisted tonsillectomy is a promising new technique for tonsillectomy as patients had less postoperative morbidity mainly pain. The surgical time required could be reduced further with experience.